Genetic sensitivity to emotional cues, racial discrimination and depressive symptoms among African–American adolescent females - Sales, Jessica M.; Brown, Jennifer L.; Swartzendruber, Andrea L.; Smearman, Erica L.; Brody, Gene H.; DiClemente, Ralph (Frontiers in Psychology, 2015)
Psychosocial stress, including stress resulting from racial discrimination (RD), has been associated with elevated depressive symptoms. However, individuals vary in their reactivity to stress, with some variability resulting from genetic differences. Specifically, genetic variation within the linked promoter region of the serotonin transporter gene (5-HTTLPR) is related to heightened reactivity to emotional environmental cues. Likewise, variations within this region may interact with stressful life events (e.g., discrimination) to influence depressive symptoms, but this has not been empirically examined in prior studies. The objective of this study was to examine whether variation in the 5-HTTLPR gene interacts with RD to predict depressive symptoms among a sample of African-American adolescent females. Participants were 304 African-American adolescent females enrolled in a sexually transmitted disease (STD) prevention trial. Participants completed a baseline survey assessing psychosocial factors including RD (low vs. high) and depressive symptomatology (low vs. high) and provided a saliva sample for genotyping the risk polymorphism 5-HTTLPR (s allele present vs. not present). In a logistic regression model adjusting for psychosocial correlates of depressive symptoms, an interaction between RD and 5-HTTLPR group was significantly associated with depressive symptomatology (AOR = 3.79, 95% CI: 1.20-11.98, p=0.02). Follow-up tests found that high RD was significantly associated with greater odds of high depressive symptoms only for participants with the s allele. RD and 5-HTTLPR status interact to differentially impact depressive symptoms among African-American adolescent females. Efforts to decrease depression among minority youth should include interventions which address racial discrimination and strengthen factors (e.g., coping, emotion regulation, building support systems) which protect youth from the psychological costs of discrimination.